Context and Implications Document for: A one‐to‐one programme for at‐risk readers delivered by older adult volunteers. Issue 3 (19th December 2013) - Fives, Allyn; Kearns, Noreen; Devaney, Carmel; Canavan, John; Russell, Dan; Lyons, Rena; Eaton, Patricia; O'Brien, Aoife
<x xml:space="preserve">Abstract</x> This guide accompanies the following article: Allyn Fives, Noreen Kearns, Carmel Devaney, John Caravan, Daniel W. Russell, Rena Lyons, Patricia Eaton and Aoife O'Brien, A one‐to‐one programme for at‐risk readers delivered by older adult volunteers, Review of Education, 10.1002/rev3.3016